A formação de futuros professores de matemática: o movimento de aprendizagem da docência em um espaço formativo para o ensino de medidas - Pozebon, Simone (2017)
This research is part of the Mathematics Education Studies and Research Group - GEPEMat, with concerns focused on the training of teachers who teach mathematics, in line with the Line of Research Training, Knowledge and Professional Development of the Graduate Program in Education of the Federal University of Santa Maria. In dealing with aspects such as human learning and development, as well as human activity, this study is based both on the basic theoretical assumptions of Vygotsky's Cultural History Theory (CHT) and Leontiev's Activity Theory - AT, when addressing the specificities of theoretical thinking and the logical-historical movement of the constitution of mathematical concepts. Regarding the perspective of the training of teachers who teach mathematics, the contributions come from authors who also anchor their proposals in this theoretical line. In this context, the main objective of this work is to investigate the process of signification of the teaching activity of the future teacher of mathematics in the movement of teaching learning in a training space for teaching measurements. As theoretical and methodological possibilities, he discusses the realization of a formative experiment, recorded by observations, field diary, audio and video recordings, with the participation of undergraduate students of Mathematics from the Federal University of Santa Maria. In order to systematize and analyze the data produced, as has been done in the GEPEMat research, the episode proposal of Moura (2004) and the unit analysis of Vigotski (2000) were used. The analysis of the data made it possible to synthesize them into four units of analysis, namely: 1) The future teacher as a subject under training, 2) The school as a social place of work of the teacher, 3) Mathematical knowledge as a guide of the teaching organization, 4) The sharing as a promoter of the quality change of actions. The data produced in the training experiment provide indications that the elements raised in the units of analysis point to principles, which, when mobilized in a training space, whose intention is the learning of teaching, can promote the signification of the teaching activity by future teachers.